Hausdorff dimension of univoque sets - Kallós Gábor; Conference for PhD Students in Computer Science (1.) (1998) (Szeged) (1999)
In this paper we present the results obtained so far for the determination of the Hausdorff dimension of the univoque set, in number systems with base number greater than 1. The investigation is based on the methods presented in [1] and [2]. We illustrate the theoretical results with interesting examples.
Keywords: Természettudományok; Számítás- és információtudomány